Titanium-based anode coating material and method for producing the same

CN117448866BActive Publication Date: 2026-10-27SHAANXI HENGYUE MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311392151.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2026-10-27
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

[0003]如CN111088493A中涉及一种钛基涂层钛阳极的制备方法,包括:对钛基体进行喷砂处理;对喷砂后的钛基体进行酸预处理,去除表面镶嵌的杂质;将处理后的钛基体放入酸液中进行酸刻蚀处理;利用超声波对酸刻蚀后的钛基体进行清洗并烘干备用;通过热分解法在处理好的钛基体上制备氧化物底层;通过电沉积法在钛基体上制备含有铱钽贵金属氧化物的活性层;对电沉积有铱钽贵金属的钛阳极放入马弗炉中高温焙烧,完成涂层钛阳极的制备,该方法制备的铱钽氧化物涂层,在纯钛表面生长均匀,纯钛基底和氧化物活性层之间结合力大,但该法制备时,钛基体表面粗糙化处理一致性差,其产生的用于结合涂层的凹坑深度差距较大,在通电过程中容易因大电流击穿导致涂层脱落

Benefits of technology

[0025]该钛基阳极涂层材料及其制备方法中,通过添加抗氧化剂和附着剂,与钛基体表面的金属原子及表面水合物结合产生范德华力和氢键,另外甲基咪唑分子的咪唑环能够与钛基体表面重金属离子形成化学键,形成稳定的络合物,即络合吸附,通过双重吸附体系能够确保涂层材料在钛基体表面的附着效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117448866B_ABST
    Figure CN117448866B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of electrochemical materials, in particular to a titanium-based anode coating material and a preparation method thereof.The titanium-based anode coating material comprises the following raw materials: graphene, a platinum compound, an antioxidant, an adhesion agent and metal powder.In the present application, the antioxidant and the adhesion agent are added to combine with the metal atoms on the surface of the titanium matrix and the surface hydrate to generate van der Waals force and hydrogen bonds.In addition, the imidazole ring of the methyl imidazole molecule can form a chemical bond with the heavy metal ions on the surface of the titanium matrix to form a stable complex, i.e., complex adsorption, and the double adsorption system can ensure the adhesion effect of the coating material on the surface of the titanium matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical materials technology, and more specifically, to a titanium-based anode coating material and its preparation method. Background Technology

[0002] Titanium-based anodes are anodes in titanium-based metal oxide coatings. Depending on the different catalytic coatings on their surfaces, they can have oxygen evolution or chlorine evolution functions. By covering them with different coating materials, titanium-based anodes can enhance their conductivity and electrocatalytic activity, promote the electrolysis reaction process, and extend the service life of the anode in different usage environments, thus achieving the expected performance.

[0003] For example, CN111088493A discloses a method for preparing a titanium anode with a titanium-based coating, including: sandblasting a titanium substrate; acid pretreatment of the sandblasted titanium substrate to remove surface-embedded impurities; acid etching of the treated titanium substrate in an acid solution; ultrasonic cleaning and drying of the acid-etched titanium substrate; preparation of an oxide underlayer on the treated titanium substrate by thermal decomposition; preparation of an active layer containing iridium-tantalum noble metal oxide on the titanium substrate by electrodeposition; and high-temperature calcination of the titanium anode with iridium-tantalum noble metal oxide in a muffle furnace to complete the preparation of the coated titanium anode. The iridium-tantalum oxide coating prepared by this method grows uniformly on the pure titanium surface, and the bonding force between the pure titanium substrate and the oxide active layer is strong. However, during the preparation by this method, the surface roughening treatment of the titanium substrate is inconsistent, and the depth of the pits used to bond the coating varies greatly. During the energization process, the coating is prone to peeling off due to breakdown caused by high current.

[0004] To ensure coating adhesion without relying entirely on pits on the titanium substrate surface, a titanium-based anodic coating material and its preparation method are proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a titanium-based anodic coating material and its preparation method to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, one objective of this invention is to provide a titanium-based anodic coating material, comprising the following raw materials in parts by weight:

[0007] 6-10 parts by weight of graphene, 21-35 parts by weight of platinum compound, 3-8 parts by weight of antioxidant, 5-11 parts by weight of adhesive and 15-22 parts by weight of metal powder;

[0008] The antioxidants include zinc butyloctyl dithiophosphate and methylimidazole, and the weight ratio of zinc butyloctyl dithiophosphate to methylimidazole is 10:1.

[0009] The adhesive comprises polyurethane and aminosilane, and the weight ratio of polyurethane to aminosilane is 7:3.

[0010] As a further improvement to this technical solution, the platinum compound is tetraammineplatinum hydrogen phosphate.

[0011] As a further improvement to this technical solution, the metal powder includes iridium powder and zirconium powder, and the mass ratio of iridium powder to zirconium powder is 1:1.

[0012] The second objective of this invention is to provide a method for preparing the titanium-based anodic coating material described above, the specific steps of which are as follows:

[0013] S1. After mixing platinum compound with metal powder, grind the mixture to produce a mixed powder, and put it into a stirring vessel with deionized water to produce a slurry.

[0014] S2. Add graphene to the slurry and perform ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid.

[0015] S3. After heating the homogenized liquid in the reactor, add antioxidants and adhesives to the reactor, and then stir and cool to produce an intermediate liquid.

[0016] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water and produce a sol-like coating.

[0017] As a further improvement to this technical solution, in step S1, the grinding produces a mixed powder with a particle size range of 45-75μm.

[0018] As a further improvement to this technical solution, in S1, the moisture content of the slurry ranges from 10-35%.

[0019] As a further improvement to this technical solution, in S2, the frequency range of ultrasonic oscillation is 20-30KHz, and the duration of ultrasonic oscillation is 10-20min.

[0020] As a further improvement to this technical solution, in step S2, a glass fiber filter is used to remove agglomerates from the homogenized liquid, and the filtration accuracy range is 80-100μm.

[0021] As a further improvement to this technical solution, in step S3, the heating temperature range is 70-85℃.

[0022] As a further improvement to this technical solution, in step S4, the moisture content of the coating ranges from 3% to 8%.

[0023] In this invention, platinum compounds and metal powders are used as conductive metal materials. By adding antioxidants, a dense zinc phosphate protective film is generated on the surface of the conductive metal material, which can effectively isolate the metal from the external environment, prevent further oxidation of the conductive metal material, and generate a high-hardness, dense protective layer with zinc phosphate as the main component. By adding an adhesive, it combines with metal atoms and surface hydrates on the titanium substrate to generate van der Waals forces and hydrogen bonds. Aminosilane can promote the adhesion of the coating material when polyurethane is bonded and cured on the titanium substrate surface. In addition, the imidazole ring of the methyl imidazole molecule can form chemical bonds with heavy metal ions on the titanium substrate surface, generating complex adsorption to form a stable complex. Through the dual adsorption system, the adhesion effect of the coating material on the titanium substrate surface can be ensured.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] In this titanium-based anodic coating material and its preparation method, by adding antioxidants and adhesives, van der Waals forces and hydrogen bonds are generated by combining with metal atoms and surface hydrates on the titanium substrate surface. In addition, the imidazole ring of the methyl imidazole molecule can form chemical bonds with heavy metal ions on the titanium substrate surface to form stable complexes, i.e., complex adsorption. The dual adsorption system can ensure the adhesion effect of the coating material on the titanium substrate surface. Attached Figure Description

[0026] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] One objective of this embodiment is to provide a titanium-based anodic coating material, comprising the following raw materials in parts by weight:

[0029] 6-10 parts by weight of graphene, 21-35 parts by weight of platinum compound, 3-8 parts by weight of antioxidant, 5-11 parts by weight of adhesive and 15-22 parts by weight of metal powder;

[0030] Furthermore, the antioxidants include zinc butyloctyl dithiophosphate and methylimidazole, and the weight ratio of zinc butyloctyl dithiophosphate to methylimidazole is 10:1. Both zinc butyloctyl dithiophosphate and methylimidazole have good antioxidant properties. Methylimidazole, which has good dispersibility, can help disperse zinc butyloctyl dithiophosphate, so that zinc butyloctyl dithiophosphate can be fully dispersed on the surface of conductive metal materials.

[0031] Furthermore, the adhesive includes polyurethane and aminosilane, with a weight ratio of 7:3 for polyurethane to aminosilane. The urethane and urea bonds of polyurethane can combine with metal atoms and surface hydrates on the titanium substrate surface to generate van der Waals forces and hydrogen bonds. When the polyurethane is bonded and cured on the titanium substrate surface, the aminosilane can promote the adhesion of the coating material. In addition, the imidazole ring of the methyl imidazole molecule can form chemical bonds with heavy metal ions on the titanium substrate surface to form a stable complex, i.e., complex adsorption. The dual adsorption system can ensure the adhesion effect of the coating material on the titanium substrate surface.

[0032] In addition, the platinum compound is tetraammineplatinum hydrogen phosphate, which has good chemical stability. When used as a platinum plating solution, the resulting coating has good adhesion and uniform texture. The metal powder includes iridium powder and zirconium powder, and the mass ratio of iridium powder to zirconium powder is 1:1. Iridium powder and zirconium powder have excellent electrical conductivity as metals, and both have good corrosion resistance.

[0033] Please see Figure 1 As shown, the second objective of this embodiment is to provide a method for preparing the titanium-based anodic coating material described above, the specific steps of which are as follows:

[0034] S1. After mixing platinum compound with metal powder, grind the mixture to produce a mixed powder with a particle size range of 45-75μm. Add the powder to a stirring tank and add deionized water to produce a slurry. The moisture content of the slurry ranges from 10-35% to ensure that other raw materials can be fully dissolved when added later. The particle size of the powder will affect the microstructure and coating performance of the coating formed on the surface of the titanium substrate.

[0035] S2. Graphene is added to the slurry and subjected to ultrasonic vibration to generate a homogenized liquid. After standing, the agglomerates in the homogenized liquid are filtered out. The frequency range of ultrasonic vibration is 20-30KHz, and the ultrasonic vibration time range is 10-20min. Ultrasonic vibration can disperse solid particles in a short time while maintaining the homogeneity and stability of the solution. Agglomerates in the homogenized liquid are filtered out using a glass fiber filter with a filtration accuracy range of 80-100μm. The glass fiber filter has the characteristics of high flow rate, strong dirt holding capacity, extremely high filtration efficiency and good chemical stability.

[0036] S3. After heating the homogenized liquid in the reactor, add antioxidants and adhesives to the reactor. After stirring and cooling, an intermediate liquid is produced. The heating temperature range is 70-85℃. Heating improves molecular activity, which facilitates the uniform mixing of raw materials.

[0037] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water to produce a sol-like coating. The water content of the coating is in the range of 3-8%. Too high a water content will affect the adhesion of the coating.

[0038] In this invention, platinum compounds and metal powders are used as conductive metal materials. By adding antioxidants, a dense zinc phosphate protective film is generated on the surface of the conductive metal material, which can effectively isolate the metal from the external environment, prevent further oxidation of the conductive metal material, and generate a high-hardness, dense protective layer with zinc phosphate as the main component. By adding an adhesive, it combines with metal atoms and surface hydrates on the titanium substrate to generate van der Waals forces and hydrogen bonds. Aminosilane can promote the adhesion of the coating material when polyurethane is bonded and cured on the titanium substrate surface. In addition, the imidazole ring of the methyl imidazole molecule can form chemical bonds with heavy metal ions on the titanium substrate surface, generating complex adsorption to form a stable complex. Through the dual adsorption system, the adhesion effect of the coating material on the titanium substrate surface can be ensured.

[0039] Based on the differences in raw material usage and process parameters during the preparation process, the following specific embodiments will further illustrate the titanium-based anodic coating material provided by the present invention.

[0040] Example 1

[0041] S1. Take 35 parts by weight of platinum compound and 15 parts by weight of metal powder, mix them and grind them to produce a mixed powder with a particle size of 75 μm. Put the powder into a stirring tank and add deionized water to produce a slurry with a moisture content of 10%.

[0042] S2. Take 10 parts by weight of graphene and add it to the slurry for ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid. The frequency of ultrasonic vibration is 20KHz and the ultrasonic vibration time is 20min. Use a glass fiber filter to filter out the agglomerates in the homogenized liquid with a filtration accuracy of 80μm.

[0043] S3. After heating the homogenized liquid in the reactor, add 8 parts by weight of antioxidant and 5 parts by weight of adhesive to the reactor. Stir and cool to produce intermediate liquid. The heating temperature is 85℃.

[0044] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water to produce a sol-like coating with a water content of 3%.

[0045] Example 2

[0046] S1. Take 28 parts by weight of platinum compound and 20 parts by weight of metal powder, mix them and grind them to produce a mixed powder with a particle size of 60 μm. Put the powder into a stirring tank and add deionized water to produce a slurry with a moisture content of 25%.

[0047] S2. Take 8 parts by weight of graphene and add it to the slurry for ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid. The frequency of ultrasonic vibration is 25KHz and the ultrasonic vibration time is 15min. Use a glass fiber filter to filter out the agglomerates in the homogenized liquid with a filtration accuracy of 90μm.

[0048] S3. After heating the homogenized liquid in the reactor, add 6 parts by weight of antioxidant and 8 parts by weight of adhesive to the reactor. Stir and cool to produce intermediate liquid. The heating temperature is 80℃.

[0049] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water to produce a sol-like coating with a water content of 5%.

[0050] Example 3

[0051] S1. Take 21 parts by weight of platinum compound and 22 parts by weight of metal powder, mix them and grind them to produce a mixed powder with a particle size of 45 μm. Put the powder into a stirring tank and add deionized water to produce a slurry with a water content of 35%.

[0052] S2. Take 6 parts by weight of graphene and add it to the slurry for ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid. The frequency of ultrasonic vibration is 30KHz and the ultrasonic vibration time is 10min. Use a glass fiber filter to filter out the agglomerates in the homogenized liquid with a filtration accuracy of 100μm.

[0053] S3. After heating the homogenized liquid in the reactor, add 3 parts by weight of antioxidant and 11 parts by weight of adhesive to the reactor. Stir and cool to produce intermediate liquid. The heating temperature is 70℃.

[0054] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water to produce a sol-like coating with a water content of 8%.

[0055] Table 1 Comparison of raw material usage in Examples 1-3

[0056] Example 1 35 15 10 8 5 Example 2 28 20 8 6 8 Example 3 21 22 6 3 11

[0057] Table 2 Comparison of process parameters in Examples 1-3

[0058]

[0059] Comparative Example 1

[0060] This comparative example uses the preparation method of Example 1, except that the antioxidant is missing, and everything else remains the same. The specific steps are as follows:

[0061] S1. Take 35 parts by weight of platinum compound and 15 parts by weight of metal powder, mix them and grind them to produce a mixed powder with a particle size of 75 μm. Put the powder into a stirring tank and add deionized water to produce a slurry with a moisture content of 10%.

[0062] S2. Take 10 parts by weight of graphene and add it to the slurry for ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid. The frequency of ultrasonic vibration is 20KHz and the ultrasonic vibration time is 20min. Use a glass fiber filter to filter out the agglomerates in the homogenized liquid with a filtration accuracy of 80μm.

[0063] S3. After heating the homogenized liquid in the reactor, add 5 parts by weight of the adhesive to the reactor, stir and cool to produce an intermediate liquid, and heat at 85°C.

[0064] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water to produce a sol-like coating with a water content of 3%.

[0065] Comparative Example 2

[0066] This comparative example uses the preparation method of Example 2, except that the antioxidant is missing. The rest remains the same, and the specific steps are similar to those of Comparative Example 1. This comparative example will not be described again.

[0067] Comparative Example 3

[0068] This comparative example uses the preparation method of Example 3, except that the antioxidant is missing. The rest remains the same, and the specific steps are similar to those of Comparative Example 1. This comparative example will not be described again.

[0069] Comparative Example 4

[0070] This comparative example uses the preparation method of Example 1, except that the adhesive is missing, and everything else remains the same. The specific steps are as follows:

[0071] S1. Take 35 parts by weight of platinum compound and 15 parts by weight of metal powder, mix them and grind them to produce a mixed powder with a particle size of 75 μm. Put the powder into a stirring tank and add deionized water to produce a slurry with a moisture content of 10%.

[0072] S2. Take 10 parts by weight of graphene and add it to the slurry for ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid. The frequency of ultrasonic vibration is 20KHz and the ultrasonic vibration time is 20min. Use a glass fiber filter to filter out the agglomerates in the homogenized liquid with a filtration accuracy of 80μm.

[0073] S3. After heating the homogenized liquid in the reactor, add 8 parts by weight of antioxidant to the reactor, stir and cool to produce intermediate liquid, and heat at 85℃.

[0074] S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. Then, the intermediate liquid is heated to remove water to produce a sol-like coating with a water content of 3%.

[0075] Comparative Example 5

[0076] This comparative example uses the preparation method of Example 2, except that the adhesive is missing. The rest remains the same. The specific steps are similar to those of Comparative Example 4, and will not be repeated here.

[0077] Comparative Example 6

[0078] This comparative example uses the preparation method of Example 3, except that the adhesive is missing. The rest remains the same. The specific steps are similar to those of Comparative Example 4, and will not be repeated here.

[0079] Table 3 Comparison of raw material usage in Comparative Examples 1-6

[0080] Comparative Example 1 35 15 10 / 5 Comparative Example 2 28 20 8 / 8 Comparative Example 3 21 22 6 / 11 Comparative Example 4 35 15 10 8 / Comparative Example 5 28 20 8 6 / Comparative Example 6 21 22 6 3 /

[0081] Table 4 Comparison of process parameters in Comparative Examples 1-6

[0082]

[0083]

[0084] Comparative Example 7

[0085] This comparative example uses the preparation method of Example 1, with the particle size set to 30 μm and the rest unchanged. The specific steps are similar to those of Example 1, and will not be repeated here.

[0086] Comparative Example 8

[0087] This comparative example uses the preparation method of Example 1, with the moisture content of the slurry set to 40%, and the rest remaining unchanged. The specific steps are similar to those of Example 1, and will not be repeated here.

[0088] Comparative Example 9

[0089] This comparative example uses the preparation method of Example 2, with the ultrasonic oscillation frequency set to 15KHz and the rest unchanged. The specific steps are similar to those of Example 2, and will not be repeated here.

[0090] Comparative Example 10

[0091] This comparative example uses the preparation method of Example 2, with the ultrasonic oscillation time set to 25 minutes, and the rest remaining unchanged. The specific steps are similar to those of Example 2, and will not be repeated here.

[0092] Comparative Example 11

[0093] This comparative example uses the preparation method of Example 2, with the filtration accuracy set to 75 μm and the rest unchanged. The specific steps are similar to those of Example 2, and will not be repeated here.

[0094] Comparative Example 12

[0095] This comparative example uses the preparation method of Example 3, with the heating temperature set to 60°C and the rest unchanged. The specific steps are similar to those of Example 3, and will not be repeated here.

[0096] Comparative Example 13

[0097] This comparative example uses the preparation method of Example 3, with the water content of the coating set to 10%, and the rest remaining unchanged. The specific steps are similar to those of Example 3, and will not be repeated here.

[0098] Table 5 Comparison of raw material usage in Comparative Examples 7-13

[0099] Comparative Example 7 35 15 10 8 5 Comparative Example 8 35 15 10 8 5 Comparative Example 9 28 20 8 6 8 Comparative Example 10 28 20 8 6 8 Comparative Example 11 28 20 8 6 8 Comparative Example 12 21 22 6 3 11 Comparative Example 13 21 22 6 3 11

[0100] Table 6 Comparison of process parameters in Comparative Examples 7-13

[0101]

[0102] Test case

[0103] The coatings prepared in Examples 1-3 and Comparative Examples 1-13 were respectively applied to titanium substrates to form titanium anodes. The titanium anodes were then placed in a 1 mol / L H2SO4 electrolyte, and the current density during energization was 2 A / cm². 2 The enhanced life test of the titanium anode was carried out under the condition of constant temperature of 50℃, and the test results were filled in Table 7 (less than 1 hour was calculated as 1 hour).

[0104] Table 7 Comparison of service life of titanium anodes prepared in the examples and comparative examples

[0105] Example 1 156 Example 2 179 Example 3 168 Comparative Example 1 128 Comparative Example 2 135 Comparative Example 3 131 Comparative Example 4 122 Comparative Example 5 130 Comparative Example 6 129 Comparative Example 7 138 Comparative Example 8 141 Comparative Example 9 151 Comparative Example 10 148 Comparative Example 11 153 Comparative Example 12 143 Comparative Example 13 145

[0106] As shown in Table 7, compared with Comparative Examples 1-13, the service life of the titanium anodes prepared in Examples 1-3 is longer than that of the titanium anodes prepared in the comparative examples, and the service life of the titanium anodes prepared in Examples is greater than 156 hours. In contrast, the service life of the titanium anodes prepared in the comparative examples with different raw material dosages and process parameters is reduced. Therefore, under the working conditions of this example, the coating prepared in the example has a better adhesion effect.

[0107] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a titanium-based anodic coating material, characterized in that, Includes the following steps: S1. Take 21-35 parts by weight of platinum compound and 15-22 parts by weight of metal powder, mix them, grind them to produce mixed powder, and put them into a stirring tank and add deionized water to produce slurry. S2. Take 6-10 parts by weight of graphene and add it to the slurry for ultrasonic vibration to generate a homogenized liquid. After standing, filter out the agglomerates in the homogenized liquid. S3. After heating the homogenized liquid in the reactor, add 3-8 parts by weight of antioxidant and 5-11 parts by weight of adhesive to the reactor, and then stir and cool to produce an intermediate liquid. S4. After the intermediate liquid is allowed to stand, it is filtered again to remove agglomerates. The intermediate liquid is then heated to remove water and produce a sol-like coating. The antioxidants include zinc butyloctyl dithiophosphate and methylimidazole, and the weight ratio of zinc butyloctyl dithiophosphate to methylimidazole is 10:

1. The adhesive comprises polyurethane and aminosilane, and the weight ratio of polyurethane to aminosilane is 7:

3.

2. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In S1, the platinum compound is tetraammineplatinum hydrogen phosphate.

3. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In S1, the metal powder includes iridium powder and zirconium powder, and the mass ratio of iridium powder to zirconium powder is 1:

1.

4. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In step S1, the grinding process produces a mixed powder with a particle size range of 45-75 μm.

5. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In S1, the moisture content of the slurry ranges from 10% to 35%.

6. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In S2, the frequency range of ultrasonic oscillation is 20-30kHz, and the duration of ultrasonic oscillation is 10-20min.

7. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In step S2, a glass fiber filter is used to remove agglomerates from the homogenized liquid, and the filtration accuracy range is 80-100μm.

8. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In S3, the heating temperature range is 70-85℃.

9. The method for preparing the titanium-based anodic coating material according to claim 1, characterized in that: In S4, the moisture content of the coating ranges from 3% to 8%.

10. A titanium-based anodic coating material prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of titanium-based coating titanium anode

    CN111088493A

  • Preparation method of visible light induced self-repairing coating based on two-dimensional titanium carbide

    CN114907755A

  • Water-based peelable coating

    US20220243087A1